Characterisation of novel TAC3 and TACR3 gene variants and polymorphisms in patients with pre-eclampsia - Stolk, Megan (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Genetics))—University of Stellenbosch, 2007.